Analysis Of The Disparity Of Narcotics Criminal Verdicts On Judex Juris And Judex Facti Verdicts - Ni’mah, Alfiyatun; Sunariyo, Sunariyo (International Journal of Applied and Scientific Research, 2024)
The study aims to determine the judge's consideration in imposing a crime on each judgment and the causes of disparities in the decisions of Judex Facti and Judex Juris judges. laws and regulations related to legal journals. The data collection technique is a literature study, and the author analyzes the collected data. The Judex Facti judge's consideration is based on fulfilling elements intentionally or without the right to unlawfully offer for sale, sell, buy, receive, intercede in buying and selling, exchanging, or delivering Class I Narcotics, and fulfilling elements of malicious trial or conspiracy to commit Narcotics and Narcotics Precursor crimes. The Judex Juris judge's decision is based on the fulfillment of the charge more subsidair, namely every narcotics abuser and for themselves. The study aims to increase insight and knowledge in criminal law related to drug crime cases to prevent and solve them.